Design and optimization of nanoemulsion formulation containing Clinacanthus nutans Lindau leaf extract for cosmeceutical application - Che Sulaiman, Intan Soraya (2017)
Plant-based cosmetics have gained more attention compared to chemical-based product in the cosmetic industry due to its safety and efficacy. However, the primary challenges are incorporation of plant based extract in the formulation owing to its hydrophobicity, instability against oxidation and also difficulties in formulating a stable carrier system. Palm kernel oil esters (PKOEs) with great skin-penetrating abilities were selected to be blended with non-ionic surfactants in the formulation process. The structure of this nanoemulsion is defined as dispersions of self-assembled PKOEs and surfactants molecules in water resulting from solubilization of surfactant micelles. A newly developed nanoemulsion system was designed to incorporate of Clinacanthus nutans (C. nutans) leaves extract for transdermal application. C. nutans or also known as Belalai Gajah is a well-known medicinal plant in tropical Asian countries that has recently attracted attention for its therapeutic characteristics. Numerous reports have documented the biological activity of C. nutans, including its anti-inflammatory, anti-viral, antioxidant and anti-cancer properties. Extract of C. nutans have been well explored for their potential as pharmaceutical agents. However, work on its use in cosmeceutical application is unknown. Formulating nanoemulsion containing C. nutans extract has much promise as an effective delivery system and leads to the potential use of this plant extract in cosmeceutical application. Preparation of C. nutans leaves extract were obtained via sequential extraction and the optimization of the extraction process were carried out using Response Surface Methodology (RSM). The optimal condition suggested by the RSM model were extraction temperature of 60 °C, at 120 min with solvent ratio (water: ethanol) of 90: 10 v/v% which yielded 23.51% of extract. However, the insolubility of this extract in the methanol testing system has limited their accessibility to antioxidant assay. Thus, in this study extracts from sequential extraction with better solubility in testing system were chosen for further used. The properties of the extract showed their suitability to be used as source of antioxidants and exhibited non-toxicity against fibroblasts cells (3T3) which established their safe properties. Design of nanoemulsions system containing C. nutans extract involved several steps including screening of the level of variables, determination of the extract solubility and finally preparation of the nanoemulsions system. Under centrifugal force, all mixture of PKOEs: guava seed oil (GSO) in ratios of 9:1, 8:2 and 7:3 containing the extract did not show any precipitation at the bottom of the test tube. The ratio of 9:1 (PKOEs: GSO) was chosen as the suitable amount of oil mixture to be used in the formulation. The effect of composition on nanoemulsions; oil and surfactant on variation of particle size was investigated using Mixture Experimental Design (MED) and Artificial Neural Network (ANN). The nanoemulsion compositions predicted by different optimization methods were different. MED (labelled as CN1) suggested an optimal formulation containing 8.13% surfactant, 5.00% oil, 1.00% xanthan gum, 0.10% bioactive extract, 0.80% preservative, and 84.97% water to produce particles with a size of 97.38 nm. Meanwhile, ANN (labelled as CN2) suggested an optimal formulation containing 10.32% surfactant, 8.00% oil, 1.00% xanthan gum, 0.10% bioactive extract, 0.80% preservative, and 79.78% water to produce particles with a size of 125.40 nm. Although the particle size obtained by MED optimization was smaller than ANN, the residual standard error (RSE) for ANN was lower than MED which were 1.17% and 2.61%, respectively. This suggested that predicted and actual values of ANN had good correlation, implying that in this work ANN approach was an effective quantitative tool to be used in optimizing formulation design. Physicochemical characterization and stability evaluation were conducted for both formulations. Based on the results, both formulations showed their suitability for transdermal applications. These formulations were found out to be in nano sized with good stability against phase separation. The formulations were also stable under storage temperature of 25 °C and 45 °C for 90 days, freeze thaw cycles and centrifugal force tests. No distinct changes were observed in the particle size of the ANN formulation, indicating that the nanoemulsion prepared was stable at the chosen optimum composition. However, the particle size of the MED formulation was slightly increased in size over the storage period, nevertheless it was still in the nano-sized range (less than 200 nm). Transmission Electron Microscopy (TEM) images for both formulations showed the spherical shape of the oil droplets in the colloidal system and the encapsulation of the bioactive extract in the oil droplets. The optimal nanoemulsion had a shear-thinning behavior in both rheological experiments (steady state and oscillatory). This direct interaction fitted the Power Law Model indicating the pseudoplastic behavior in the system and gel structure existence which was one of the criteria in the formulation of transdermally applied cosmetics. Both formulations had pH values within the human skin range which was good for transdermal use. Taking into account the physicochemical characterization of both optimal nanoemulsions, ANN formulation labeled as CN2 was chosen to be the optimal composition in designing the C. nutans nanoemulsion. CN2 exhibited non-irritant property with a Human Irritancy Equivalent score of 0.13. In vivo ultrasound attributes of the skin study for CN2 showed that the collagen content increased significantly with the application of the C.nutans nanoemulsion among all 21 volunteers during the 21 d of the treatment period. The biophysical attributes of skinstudies demonstrated that skin hydration increased without any increment in transepidermal water loss. Thus, a stable C. nutans nanoemulsion was successfully developed which had the ability to promote collagen production in human skin and improved the skin barrier function and hence could be potentially used as a system for the delivery of natural antioxidant in cosmetic products.